Diet and prey selectivity in co-occurring eelpout fish and bythograeid crabs in a deep-sea hydrothermal vent community - Davis, Deidric B.; Smith, Nancy (PeerJ, 2025)
Understanding the trophic ecology of deep-sea communities is central to assessing ecological structure and function, which is often lacking in remote oceanographic environments such as hydrothermal vents. Using stomach content analysis coupled with published stable isotope data, we assessed diet and prey selectivity in two common predators, eelpouts (Pyrolycus manusanus) and crabs (Austinograea alayseae), from a South Pacific deep-sea hydrothermal vent community. Using specimens collected during a cruise in 2007, we found that eelpouts strongly preferred alvinocarididshrimp. This observation is s upported by the Ivlev index, which measures the selection of prey in relation to their abundance or availability. Crabs exhibited a diverse diet, including polychaetes and shrimp, suggesting a scavenging or omnivorous feeding strategy. Due to the lack of intact stomach contents in the crab, we were unable to apply the Ivlev method to quantify its prey selectivity. Our results emphasize the need to combine stomach contents, stable isotope analysis, and other complementary methodologies, to elucidate the role of predators in deep-sea food webs. In sum, our study underscores the importance of direct stomach content examination in revealing trophic relationships in hydrothermal vent systems.
Keywords: Trophic ecology; Hydrothermal vents; Prey selectivity; Feeding guilds; Ivlev index; Eelpout; Gut content analysis; Manus basin